2006
DOI: 10.1111/j.1365-2656.2006.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of environmental stress and inbreeding on reproductive traits in a wild bird population

Abstract: Summary1. Conservation biologists are concerned about the interactive effects of environmental stress and inbreeding because such interactions could affect the dynamics and extinction risk of small and isolated populations, but few studies have tested for these interactions in nature. 2. We used data from the long-term population study of song sparrows Melospiza melodia on Mandarte Island to examine the joint effects of inbreeding and environmental stress on four fitness traits that are known to be affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 34 publications
8
86
3
Order By: Relevance
“…However, the direction and magnitude of HFC differed among years and they were only significantly explained by multilocus heterozygosity calculated at all markers or the panel of neutral markers, but not by genetic diversity estimated at the subset of putatively functional loci. We also found a highly significant positive relationship between selection differentials ( S ) for heterozygosity and annual accumulated precipitation, which indicates that interannual differences in HFC may be explained by the different environmental conditions to which individuals are exposed each year (Armbruster & Reed, 2005; Fox & Reed, 2011; Marr et al., 2006). Hence, our results reinforce the expectation of stronger selection under adverse environmental conditions in wild populations (Endler, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the direction and magnitude of HFC differed among years and they were only significantly explained by multilocus heterozygosity calculated at all markers or the panel of neutral markers, but not by genetic diversity estimated at the subset of putatively functional loci. We also found a highly significant positive relationship between selection differentials ( S ) for heterozygosity and annual accumulated precipitation, which indicates that interannual differences in HFC may be explained by the different environmental conditions to which individuals are exposed each year (Armbruster & Reed, 2005; Fox & Reed, 2011; Marr et al., 2006). Hence, our results reinforce the expectation of stronger selection under adverse environmental conditions in wild populations (Endler, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that the association between genetic diversity (or inbreeding) and different components of fitness become stronger under stressful conditions (Armbruster & Reed, 2005; Fox & Reed, 2011), but most evidence on this respect comes from experimental approaches and only a few studies have analyzed such interactions in wild populations (Forcada & Hoffman, 2014; Marr et al., 2006; Szulkin & Sheldon, 2007). Here, we quantified the relationship between heterozygosity and fitness along an environmental continuum, comprising harsh (wet–cool) and benign (dry–warm) years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inconsistency between studies may be partially explained by the fact that HFCs could become meaningful only under particular environmental conditions; (Chapman et al 2009) these may be revealed in competitive environments and appear non-significant under favorable conditions. Indeed, environmental factors such as thermal stress, limited food availability, parasite presence and harsh weather conditions have been found to strengthen the association between heterozygosity and fitness with more pronounced correlations arising under stressful environmental conditions (Lesbarreres et al 2005;Da Silva et al 2006;Marr et al 2006;Fox and Reed 2011;Voegeli et al 2012;Forcada and Hoffman 2014;Ferrer et al 2016). However, this avenue of research has received limited attention to date and has rarely been tested in experimental studies.…”
Section: Introductionmentioning
confidence: 98%